Corn Silk (Zea mays L.) Extract Is as Effective as Metformin in Reducing Blood Glucose Levels in Diabetic Mice - Said, Amanulloh Naufal; Mashudi, Sugeng; Mas’udah, Anni Fithriyatul; Erlisna, Rachel Indah Putri Ayu (FORIKES, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and associated with serious complications affecting multiple organs. The increasing global prevalence of diabetes has encouraged exploration of alternative natural therapies with antihyperglycemic potential. This study aimed to determine the effectiveness of corn silk (Zea mays L.) extract in reducing blood glucose levels in diabetic mice. An experimental study was conducted using two groups of mice, each consisting of six animals. Group I received corn silk extract, while Group II received metformin. Blood glucose levels were measured after treatment, and differences between groups were analyzed using the Mann–Whitney test. Both corn silk extract and metformin reduced blood glucose levels in diabetic mice. Statistical analysis showed no significant difference in the mean reduction of blood glucose levels between the two groups (p = 0.083). Corn silk extract demonstrated a glucose-lowering effect comparable to metformin in diabetic mice, indicating its potential as a natural antihyperglycemic agent.Keywords: corn silk; diabetes mellitus; metformin